Microphysiological system with integrated sensors to study the effect of pulsed electric field - Bakute, Neringa; Andriukonis, Eivydas; Kasperaviciute, Kamile; Dobilas, Jorunas; Sapurov, Martynas; Mozolevskis, Gatis; Stirke, Arunas (Nature Research, 2024)
This study focuses on the use of pulsed electric fields (PEF) in microfluidics for controlled cell studies. The commonly used material for soft lithography, polydimethylsiloxane (PDMS), does not fully ensure the necessary chemical and mechanical resistance in these systems. Integration of specific analytical measurement setups into microphysiological systems (MPS) are also challenging. We present an off-stoichiometry thiol-ene (OSTE)-based microchip, containing integrated electrodes for PEF and transepithelial electrical resistance (TEER) measurement and the equipment to monitor pH and oxygen concentration in situ. The effectiveness of the MPS was empirically demonstrated through PEF treatment of the C6 cells. The effects of PEF treatment on cell viability and permeability to the fluorescent dye DapI were tested in two modes: stop flow and continuous flow. The maximum permeability was achieved at 1.8 kV/cm with 16 pulses in stop flow mode and 64 pulses per cell in continuous flow mode, without compromising cell viability. Two integrated sensors detected changes in oxygen concentration before and after the PEF treatment, and the pH shifted towards alkalinity following PEF treatment. Therefore, our proof-of-concept technology serves as an MPS for PEF treatment of mammalian cells, enabling in situ physiological monitoring. © The Author(s) 2024. --//-- This is an open-access article Bakute, N., Andriukonis, E., Kasperaviciute, K. et al. Microphysiological system with integrated sensors to study the effect of pulsed electric field. Sci Rep 14, 18713 (2024). https://doi.org/10.1038/s41598-024-69693-w published under the CC BY-NC-ND 4.0 licence.
A.S. acknowledges to the ERDF PostDoc project No. 1.1.1.2/VIAA/4/20/739. We acknowledge Vilius Vertelis for electrode deposition, Skirmantas Kersulis for expertise in PEF, and Agne Damarackaite for her assistance in performing the experiments. The Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Microfluidics; Microphysiological system; OSTE; Pulsed electric field; Sensors; PDMS